Ampicillin susceptibility and ampicillin-induced killing rate of Escherichia coli. - Thonus, I P (1982)
The killing rate induced by ampicillin was determined in 20 strains of Escherichia coli. The apparent generation rate constant for each E. coli showed a characteristic concentration-dependent course. This course can be mathematically described and is determined by four parameters. Three of these parameters determine the speed of the process, and the fourth parameter determines a minimal concentration. The susceptibility of the strains, measured as the minimal inhibitory concentration by an agar dilution method, correlated with the minimal concentration and with a minimal inhibitory concentration calculated from the curve, but not with the rate-determining parameters.